2016
DOI: 10.1542/peds.2015-2447
|View full text |Cite
|
Sign up to set email alerts
|

Cheerleading Injuries in United States High Schools

Abstract: BACKGROUND AND OBJECTIVES:Approximately 400 000 students participate in US high school cheerleading annually, including 123 386 involved in competitive spirit squads. The degree of athleticism and the difficulty of cheerleading skills have increased in recent decades, renewing safety concerns. This study describes the epidemiology of high school cheerleading injuries and compares cheerleading injury rates and patterns relative to other sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
2
20
0
3
Order By: Relevance
“…Similar rates have been recorded in high school and university student populations ( Baker & Good, 2014 ; Halstead & Walter, 2010 ) implying that the nature of play demanded by these sports may place athletes at a greater risk of sustaining a head injury ( McAllister et al, 2012 ). For example, in a high-risk sport like competitive cheerleading, concussions account for over 30% of all injuries sustained ( Currie, Fields, Patterson, & Comstock, 2015 ) despite the non-contact nature of competition.…”
Section: Introductionmentioning
confidence: 99%
“…Similar rates have been recorded in high school and university student populations ( Baker & Good, 2014 ; Halstead & Walter, 2010 ) implying that the nature of play demanded by these sports may place athletes at a greater risk of sustaining a head injury ( McAllister et al, 2012 ). For example, in a high-risk sport like competitive cheerleading, concussions account for over 30% of all injuries sustained ( Currie, Fields, Patterson, & Comstock, 2015 ) despite the non-contact nature of competition.…”
Section: Introductionmentioning
confidence: 99%
“…6 Describing the incidence of concussion in interscholastic sports is essential to identifying those at greatest risk of injury and where injury-reduction interventions should be targeted. When sports are evaluated independently, those with high concussion rates include rugby, 12 football, 13 girls' soccer, 13 cheerleading, 14,15 and boys' wrestling. 13 Numerous authors 7,13,16,17 have reported concussion rates across various samples of high school sports.…”
mentioning
confidence: 99%
“…All 3 systems have been in operation for 10 or more years and have been used to characterize injuries in a number of organized HS and collegiate sports. [24][25][26][27][28][29][30] Data from all 3 systems are reviewed and used by national sport organizations' (National Federation of State High School Associations [NFHS] and NCAA) medical advisory and sport rules committees on a regular basis to evaluate current and future sport rules, protective equipment requirements, medical care, and safety policies. For this study, internal organ injuries were defined as affecting the abdominal and thoracic internal organs (eg, kidney, lung) due to direct contact (contact with person, apparatus, surface, or object) and resulting in medical care and time loss of at least 1 day (RIO and ISP) or semipermanent or permanent disability or death (NCCSIR).…”
Section: Methodsmentioning
confidence: 99%